2014
DOI: 10.1016/j.jped.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E concentration in human milk and associated factors: a literature review

Abstract: Alpha-tocopherol concentration in milk decreases during lactation, until the mature milk appears. To confirm the influence of some maternal and child variables on milk vitamin E content, further studies with adequate design are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 32 publications
(59 reference statements)
2
27
0
Order By: Relevance
“…In general, comparing the results with the literature, it is clear that the levels of vitamin in the milk are consistent with studies involving infants in developed countries, and in situations of food safety 7 . The concentration of alpha-tocopherol in colostrum milk was higher than that of the Polish infants, 6 lower than that of a study conducted in Spain 9 , and similar to the concentration found in Brazil 19 …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In general, comparing the results with the literature, it is clear that the levels of vitamin in the milk are consistent with studies involving infants in developed countries, and in situations of food safety 7 . The concentration of alpha-tocopherol in colostrum milk was higher than that of the Polish infants, 6 lower than that of a study conducted in Spain 9 , and similar to the concentration found in Brazil 19 …”
Section: Discussionsupporting
confidence: 87%
“…Although the amount of alpha-tocopherol offered to infants is reduced with the advancement of the phases of lactation, there is an increase in the volume of milk consumed by the newborn to meet the nutritional requirement 7 . In this study, the mature milk has not provided the AI of vitamin E for the infant.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The changes in milk composition depending on different factors, such as stage of lactation or duration of the feeding [ 24 , 25 , 26 ], maternal diet, supplementation, and nutritional status [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] have been demonstrated. In recent years, association studies have found other potential factors influencing the concentrations of vitamins in breast milk, including maternal socio-economic [ 36 , 37 , 38 ], obstetric, or physiological factors [ 24 , 35 , 36 , 37 , 39 , 40 ]. Indeed, maternal socio-economic and obstetric factors are changing in China, such as the rate of cesarean delivery, which increased from 3.4% in 1988 to 39.3% in 2008 [ 41 ] and to 54.5% in 2011 [ 42 ]; as well as the increase in inappropriate gestational weight gain (GWG).…”
Section: Introductionmentioning
confidence: 99%